Diffusion Equilibrium for Ammonia in the Kidney of the Acidotic Dog - Stone, William J. (1967)
Inflow of preformed ammonia in arterial blood, renal production of ammonia, outflow of ammonia in renal venous blood, and urinary excretion of ammonia were measured during the infusion of (15)NH(4)Cl into one renal artery of dogs with chronic metabolic acidosis. Our results show that the specific activity of ammonia measured in the urine and that calculated in the renal pool agree within 95%. Pool specific activity is obtained by dividing the rate of infusion of isotope by the pool turnover rate, i.e., the sum of the rate of ammonia output in the urine and that in renal venous blood. An average of 35% of urinary ammonia is derived from arterial ammonia in these experiments. We conclude that ammonia is distributed evenly throughout all phases of the kidney within a period less than the transit time of blood through the kidney. Furthermore, from the proportion of urinary ammonia we found to be derived from preformed arterial ammonia (35%), and from our previous demonstration that 73% of urinary ammonia derives from deamidation and/or deamination of plasma glutamine, alanine, glycine, and glutamate, we can account for all of the ammonia that leaves the kidney in renal venous blood and in urine.